ACA Exchange Competitiveness In California. Issue 2 (September 2017) - Weinberg, Micah; Kallerman, Patrick
Abstract: California's implementation of the Affordable Care Act (ACA) has been the most successful in the nation and is, in many ways, a model of how a managed competition marketplace is expected to work. In particular, the state's decision to structure its marketplace as an active purchaser has contributed to premium increases that are lower than in almost all other states. This report on the performance of the ACA marketplace in California examines the effects of concentration and consolidation factors, the breadth of enrollment, and the impact of competition on the cost of health insurance and the options available to consumers across the many diverse regions of the state, in the context of an active purchaser exchange structure interacting with the regulations of federal law and with local market dynamics. It concludes that the relative concentrations of insurers and particularly of providers in the different rating regions of the state are the fundamentals that matter most in the effort to bend the health insurance cost curve.